2015
DOI: 10.1155/2015/301562
|View full text |Cite|
|
Sign up to set email alerts
|

EOLA1 Inhibits Lipopolysaccharide-Induced Vascular Cell Adhesion Molecule-1 Expression by Association with MT2A in ECV304 Cells

Abstract: Our research group firstly discovered endothelial-overexpressed lipopolysaccharide-associated factor 1 (EOLA1, GenBank number AY074889) as a lipopolysaccharide (LPS) responsive gene in ECV304 cells. The previous studies have further demonstrated the association of EOLA1 with metallothionein 2A (MT2A), while the role of EOLA1 during LPS-induced inflammatory response in ECV304 cells is unknown. In this report, we determined the subcellular localization of EOLA1 and the regulatory capacity of EOLA1 on vascular ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Meanwhile, we found that when the baseline level of systemic inflammation (HsCRP, PCT, IL-6, WBC, and NE%) and the important factors affecting ulcer healing (ABI, hemoglobin, and albumin) were consistent between the two groups, EOLA1 was expressed highly in the skin tissues of the acute wound in DFU but lowly in those of the chronic wound. On the contrary, the expression of some important molecules (e.g., NF- κ B and IL-6) in inflammatory activation pathways was higher in the CW group than in the AW group, which is consistent with the previous studies [8, 9]. This suggests that EOLA1 may be involved in the negative regulation of local chronic inflammatory response in DFU.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, we found that when the baseline level of systemic inflammation (HsCRP, PCT, IL-6, WBC, and NE%) and the important factors affecting ulcer healing (ABI, hemoglobin, and albumin) were consistent between the two groups, EOLA1 was expressed highly in the skin tissues of the acute wound in DFU but lowly in those of the chronic wound. On the contrary, the expression of some important molecules (e.g., NF- κ B and IL-6) in inflammatory activation pathways was higher in the CW group than in the AW group, which is consistent with the previous studies [8, 9]. This suggests that EOLA1 may be involved in the negative regulation of local chronic inflammatory response in DFU.…”
Section: Discussionsupporting
confidence: 91%
“…EOLA1 is weakly expressed in leukocytes and endothelial cells under a resting state, and such expression can be significantly increased after stimulation with lipopolysaccharide (LPS). EOLA1 has the functions of promoting cell growth, inhibiting apoptosis, and downregulating the secretion of immune-inflammatory factors such as intracellular interleukin-6 (IL-6) and intercellular adhesion molecule-1 (ICAM-1) [8, 9]. In addition, EOLA1 is associated with cell growth, and the growth of ECV304 cells is significantly slowed down after the inhibition of EOLA1 expression [10].…”
Section: Introductionmentioning
confidence: 99%
“…MT2A could regulate cell inflammatory response through inhibition of nuclear factor-κB (NF-κB) [ 55 ], and endothelial-overexpressed LPS-associated factor-1 (EOLA1) [ 56 ]. Inflammatory cytokines are released by oxidative stress [ 57 ], whereas MT2A could inhibit the activation of pro-inflammatory cytokines, such as IL-6, IL-12 and TNF-α [ 15 ].…”
Section: Mt2a Functionmentioning
confidence: 99%
“…EOLA1 was reported to mediate the expression of several proteins such as IL-6 and VCAM-1 under the stimulus of LPS [10,25]. Previously, a fraction of ASCH proteins were speculated to conduct transcriptional or translational roles [11], and the nuclease activity of Zm ASCH was suggested to be involved in the removal of cellular RNAs, and thus, regulation of transcriptional and translational processes [14].…”
Section: Discussionmentioning
confidence: 99%